2014
DOI: 10.1186/bf03351762
|View full text |Cite
|
Sign up to set email alerts
|

A sandpile experiment and its implications for self-organized criticality and characteristic earthquake

Abstract: We have performed an experiment in which a conical sandpile was built by slowly dropping sand onto a circular disk through a funnel with a small outlet. Avalanches (sand dropping off the disk) occurred, the size and the number of which were observed. It was seen that the behavior of avalanches (frequency-size distribution) was determined solely by the ratio of grain size to disk size, which is consistent with earlier studies. We categorize the behavior into three types: (1) the self-organized criticality (SOC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…This behavior suggests that the bed does not rearrange itself to attain a state that is just at the limit of stability, but rather can jump to a new state that is capable of withstanding further flow increases. We believe the “jumpy” nature of the channel response, analogous to phenomena associated with critical limit states in other media [e.g., Yoshioka , 2003], contributes significantly to the variability observed in the jamming plot.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior suggests that the bed does not rearrange itself to attain a state that is just at the limit of stability, but rather can jump to a new state that is capable of withstanding further flow increases. We believe the “jumpy” nature of the channel response, analogous to phenomena associated with critical limit states in other media [e.g., Yoshioka , 2003], contributes significantly to the variability observed in the jamming plot.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they found anomalously large quasi-periodic avalanches, that exceeded the expectations for large events in SOC (see, e.g. Fig.4 in [28]). The reason for this is that real sandgrains have a tendency to keep on moving once they start doing so, dragging other grains, and facilitating the emergence of huge avalanches.…”
mentioning
confidence: 83%
“…It can be shown that avalanche size and frequency follow a power law with exponent of ζ close to −1 [ Hergarten , 2002]. The notion that addition of a single grain may induce avalanches with a wide range of size distributions have been confirmed in laboratory experiments using sand or rice grains [ Yoshioka , 2003; Held et al , 1990; Lörincz and Wijngaarden , 2007], however, the resulting values of power laws |ζ| were typically higher (between 1.1 and 2.5) than predicted by the theoretical BTW‐sandpile model. This difference in power law values indicates that the frequency of large avalanches is lower in real systems and the redistribution mechanism in the sandpile model is too simplified, mainly due to frictional forces reducing stress release in real sandpiles [ Hergarten , 2003].…”
Section: Introductionmentioning
confidence: 99%